Deadly Dermatologic Diseases Clinicopathologic Atlas and Text - Crowe, David R.; Morgan, Michael; Somach, Stephen; Trapp, Kara (Springer International Publishing : Imprint: Springer, 2016)
This new edition of the popular 2007 original text is completely updated with full color, high quality photographs and illustrations for easy reference by dermatologists, dermatology residents, primary care and emergency medicine physicians. Presented in an easily accessible manner, this second edition discusses more than 40 diseases that could lead to serious medical consequences, including death. Organized alphabetically and focusing more heavily on dermatopathology than its predecessor, Deadly Dermatologic Diseases, Second Edition contains a single clinical photograph accompanied by three photomicrographs that detail the diagnostic features of each case. Additionally, each subsection discusses a disease prognosis with a current bibliography in a succinct, bulleted manner, making this a must-have reference for clinicians and pathologists alike.